Food consumption score and the Nexus of maternal nutritional status among pregnant women in Gamo Zone, South Ethiopia - Fikadu, Teshale; Tamiru, Dessalegn; Ademe, Beyene Wondafrash (Frontiers in Nutrition, 2025)
BackgroundFood consumption score is an indicator used to evaluate food security, ensuring that individuals have reliable access to sufficient, safe, and nutritious food that meets their dietary needs and preferences for an active and healthy life. Poor nutrition during the first 1,000 days of life can result in developmental delays, stunted growth, cognitive impairments, and a higher risk of chronic diseases later in life. This study, therefore, aims to evaluate the level of food consumption scores and its associated factor among pregnant women.MethodsA community-based cross-sectional study was conducted among 638 randomly selected pregnant women from October to March 2023 at the Arba Minch Health and Demographic Surveillance site in Southern Ethiopia. Data were collected using a pre-tested, interviewer-administered structured questionnaire. Modified Poisson regression was employed to measure prevalence ratios, while both bivariate and multivariable analyses were performed to identify potential variables for further analysis and to determine factors associated with an acceptable food consumption score, respectively.ResultAmong the 638 pregnant women, 8.15% (95% CI: 6.26, 10.55) had poor, 14.89% (95% CI: 12.33, 17.87) had borderline, and 76.96% (95% CI: 73.52, 80.07) had acceptable food consumption scores While 31.97% of the pregnant women were suffering from under nutrition. Acceptable food consumption score was higher among women who were urban dwellers (APR = 1.09; 95% CI: 1.02, 1.20), in higher economic status (APR = 1.05; 95% CI: 1.01, 1.16), had planned pregnancy (APR = 1.13; 95% CI: 1.02, 1.25), were exposed to mass media (APR = 1.19; 95% CI: 1.07, 1.31), had a vegetable garden (APR = 1.14; 95% CI: 1.04, 1.25), attend health facility for antenatal care (APR = 1.13; 95% CI: 1.02, 1.26), and those who consumed food four or more times per day (APR = 1.23; 95% CI: 1.11, 1.36). Also the level of acceptable food consumption score increased by 2, 3, and 4% for every one-unit increase in BMI (APR = 1.02; 95% CI: 1.01, 1.04), MUAC in cm (APR = 1.03; 95% CI: 1.01, 1.05), and gestational age in weeks (APR = 1.04; 95% CI: 1.01, 1.07), respectively.ConclusionNearly one-third and three-fourths of the pregnant women were undernourished and had acceptable food consumption scores, respectively. Factors associated with acceptable food consumption scores included place of residence, wealth status, planned pregnancy, exposure to mass media, having a vegetable garden, attending antenatal care at health facilities, consuming four or more meals daily, and gestational age. Thus addressing these factors is crucial for improving FCS among pregnant women. Furthermore, efforts should be directed toward increasing media exposure, boosting household income, promoting vegetable gardening, and improving planned pregnancies and antenatal care visits.